Administration, labor, and love. (January 2023) - Ginther, April
Great opportunities for language testing practitioners are enabled through language program administration. Local language tests lend themselves to multiple purposes—for placement and diagnosis, as a means of tracking progress, and as a contribution to program evaluation and revision. Administrative choices, especially those involving a test, are strategic and can be used to transform a program's identity and effectiveness over time.